1975
DOI: 10.1136/hrt.37.11.1161
|View full text |Cite
|
Sign up to set email alerts
|

Creatine kinase release in acute myocardial infarction: correlation with clinical, electrocardiographic, and pathological findings.

Abstract: Creatine kinase (CK) cardiogram, and serum enzyme changes. Initially serum CK activity in all patients was still within the normal range (< 40 mU/ml). Patients who had had intramuscular injections, direct current shock, or other possible cause of increase in serum CK activity were excluded from the study.Blood for CK determinations was taken at one-, two-, or three-hourly intervals from the time of admission until CK activity had either returned to normal or, in patients who died, was decreasing. CK activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
13
1
2

Year Published

1979
1979
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(20 citation statements)
references
References 4 publications
4
13
1
2
Order By: Relevance
“…Several methods are available for studies of the time course in acute myocardial infarction (Inoue et al, 1977;Mathey et al, 1975;von Essen et al, 1979). All of them are indirect and inexact.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods are available for studies of the time course in acute myocardial infarction (Inoue et al, 1977;Mathey et al, 1975;von Essen et al, 1979). All of them are indirect and inexact.…”
Section: Discussionmentioning
confidence: 99%
“…. 1977;Cobb et al, 1979;Mathey et al, 1975;Sobel et al, 1972;Swain et al, 1980;Vatner et al, 1978). Diagnosis of chronic infarction is not difficult (Bodenheimer et al, 1975(Bodenheimer et al, , 1976Hillis and Braunwald, 1977;Selwyn er al., 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Kronenberg et al3 reported infarct extension associated with ST elevation in 33% of 27 patients, six of whom died. Mathey et al 4 found that abnormal CK release curves suggesting infarct extension were present in 62% of 40 patients. In a postmortem study, Hutchins and Bulkley5 found histologic evidence of recent foci of necrosis around an infarct in 17% of 76 hearts.…”
mentioning
confidence: 99%